PREVALENCE OF HAEMOPARASITES IN SNAKES FROM AN EX-SITU CONSERVATION ENVIRONMENT (Revista Científica Ciencias Naturales y Ambientales, 2025)
The study was conducted at the breeding and reproduction center of the National Institute of Public Health and Research (INSPI) in Guayaquil, Ecuador, with the aim of determining the prevalence of hemoparasites in captive snakes. Blood samples from 30 snakes of different species were analyzed using blood smear and Giemsa staining techniques.The research is of significant importance due to the high prevalence of hemoparasites in reptiles and their impact on the health of these animals. Moreover, the study was conducted at a center breeding venomous snakes for antivenom production, making monitoring of these animals' health crucial to ensure the quality and safety of the produced antivenoms. The results revealed an 80% prevalence of hemoparasites in the studied snakes, with Hepatozoon being the most common. An association was found between the presence of hemoparasites and a hematocrit level below 15%, as well as with a captivity duration ranging from 1 month to 3 years. Most of the positive snakes originated from the province of Manabí.This study underscores the importance of monitoring the health of captive snakes and conducting hemoparasite detection exams to prevent disease spread. Further studies are recommended to better understand the relationship between hemoparasites and snake health, and to implement preventive measures to control the spread of these infections in breeding center.
Keywords: Antivenoms, Captivity, Hemoparasites, Snakes, Prevalence.